Enhanced Ca2+-dependent SK-channel gating and membrane trafficking in human atrial fibrillation - Heijman, Jordi; Zhou, Xiao-Bo; Morotti, Stefano; Molina, Cristina E.; Abu-Taha, Issam H.; Tekook, Marcel; Jespersen, Thomas; Zhang, Yiqiao; Dobrev, Shokoufeh; Milting, Hendrik; Gummert, Jan; Karck, Matthias; et al. (Circulation research, 2023)
Small-conductance Ca2+-activated K+ (SK)-channel inhibitors have antiarrhythmic effects in animal models of atrial fibrillation (AF), presenting a potential novel antiarrhythmic option. However, the regulation of SK-channels in human atrial cardiomyocytes and its modification in patients with AF are poorly understood and were the object of this study.